Influence of polyester fabric with infrared emissive additives on cell metabolism - He Peng Fei; Veerakumar Arumugam; Aleksander Góra; Vitali Lipik (Communications in Development and Assembling of Textile Products)
Functional fabrics with effects of influencing the metabolism and energy supplying are of great interest and may extensively be applied in wellness and sport apparel. In this work, three different combinations of additives such as silicon oxide doped with 10% of iron oxide III, 10% of graphene and 10% calcium hydroxyapatite were prepared, each combination was compounded separately with polyester, and pellets were extruded with additive weight around 4%. Melt spun multifilament yarns (130D/48f) were produced from the prepared pellets. Further, three knitted fabrics from a yarn with additives and one control fabric from the yarn without additives were developed for comparison and analysis. Infrared emissivity test result showed that fabrics with functional additives have significantly higher effective emissivity (0.997 to 1.006) than the reference fabric (0.909) for wavelength 5-14 µm. Moreover, spectral emissivity of fabrics with additives are relatively high at peak human IR emission wavelength (8-14 µm). As a key signal molecule that is involved in certain physiological pathways, nitric oxide (NO) generation was assessed by co-culturing with human skeletal muscle cells (HMSCs). It is observed that selected additives in the fabric lead to 15%-40% increase of nitrite levels in muscle cells after 24 and 72 hours of exposure and the best among them were graphene containing additives. Besides, it is also discovered that additives in the fabric increase mitochondrial biogenesis, which is proved by the increase of mitochondrial copy number by a factor of 1.25. The mitochondrial biogenesis may be a possible pathway activated by nitric oxide and potentially accelerate the energy expenditure. The observations in the cell study indicated the potential biological effects of the fabric with selected functional additives.